Effect of feeding concentrate on the reproductive efficiency of repeat breeder cows at Baghabari milk shed area - Islam, MS; Deb, Gk; Habib, MA; Ershaduzzaman, M; Ali, Md Yousuf; Kabir, MH; Akter, Most Sumona; Aktaruzzaman, M; Uddin, M Salah; Rahman, SM; Afroz, MF (Asian Journal of Medical and Biological Research, 2018)
A total of nine Repeat Breeder (RB) cows consisting three cows in each of the three treatment groups were selected at farmer’s house of Nukali village of Sahjadpur Upazila under Sirajgonj district to know the feeding effect of concentrate feed on reproductive efficiency of RB cows. Concentrate feeds were given to the RB cows based on their body weight and milk production. Same management like housing, watering and quantity of green grasses and straw were ensured during the experimental period. Heat detection of cow was done by Draminski Estrous Detector (DRAMINSKI) to perform artificial insemination in standing heat period. Experimental diet samples were tested for chemical compositions in the laboratories. Data were statistically analyzed by the computer software program of SPSS. Days open or calving to conception interval were 13.00±3.51, 9.33±1.20 and 15.33±1.45 months for treatment group T1, T2 and T3, respectively. All experimental cows (100%) of treatment group one (T1) were become pregnant whereas no cows (0%) were conceived in treatment group (T3). Mean conception rate of all experimental cows was 0.56±0.18 with no significant difference. The results from the present study showed that dietary status of crossbred dairy cow can improve the reproductive efficiency like the conception rate RB cows. It’s would be concluded that diet containing optimum level of CP, Ca and P might be played a vital role for maximum conception rate of RB cows which clearly indicates the dietary intervention effect for improving the breeding efficiency of repeat breeder cows. Asian J. Med. Biol. Res. March 2018, 4(1): 137-140